The Application of Cooperative Team Games Tournament (TGT) Method for Improving Quadratic Equation Learning Outcomes in Vocational High Schools - Wati, Sri; Aminudin, Mohamad (JURNAL PENDIDIKAN MATEMATIKA, 2024)
Abstarct. This study aims to improve the learning outcomes of vocational high school (SMK) students in quadratic equation material through the implementation of the Teams Games Tournament (TGT) learning model. The research method employed was Classroom Action Research (CAR), conducted in three cycles, each consisting of planning, implementation, observation, and reflection. The subjects of this study were 10th-grade students at SMKS Muhammadiyah 4 Sukorejo Kendal. Data were collected through learning outcome tests and classroom activity observations. The findings indicate that the TGT model effectively enhances students' understanding of quadratic equations, as evidenced by the increase in average test scores and active participation in group discussions and academic competitions. This research supports the use of game-based cooperative learning to boost student motivation and academic achievement in vocational education. Keywords: Teams Games Tournament (TGT), learning outcomes, quadratic equations, classroom action research, vocational high school.